Fungsi Legislasi Badan Permusyawaratan Desa (BPD) dalam Pembentukan Peraturan Desa - Dodik Prihatin AN (Fakultas Hukum Universitas Islam Jember, 2017)
Village regulations are village-level legal products established by the village head along with the Village Consultative Board in the context of the administration of the village administration. Village regulations are a further elaboration of the higher laws by taking into account the socio-cultural conditions of local communities. The Village Consultative Body (BPD), which then called BPD, has the function of establishing village regulations with village heads, accommodating and channeling the aspirations of the community, therefore BPD as a deliberative body originating from the village community, in addition to carrying out its function as a bridge between the village head and the village community, primarily, the function of representation (Representative). The role of the Village Consultative Body is to establish village regulations with village heads, to accommodate and channel the aspirations of the people. The Village Consultative Body is a representative of the villagers determined by deliberation and consensus.